2018
DOI: 10.1002/art.40661
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tumor Necrosis Factor Inhibitor Versus Nonsteroidal Antiinflammatory Drug Treatment on Radiographic Progression in Early Ankylosing Spondylitis: Its Relationship to Inflammation Control During Treatment

Abstract: Objective. To investigate the impact of tumor necrosis factor inhibitor (TNFi) treatment and inflammation control on radiographic progression in early ankylosing spondylitis (AS) over 4 years.Methods. We included a total of 215 patients with early AS (symptom duration <10 years) treated with TNFi (the TNFi group; n = 135) or with nonsteroidal antiinflammatory drugs (NSAIDs) (the control group; n = 80). Two blinded readers assessed radiographic progression using the modified Stoke Ankylosing Spondylitis Spine S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
2
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 28 publications
1
62
2
7
Order By: Relevance
“…In a recent study, Park et al showed that early TNFi treatment can reduce radiographic progression by inflammation control. 15 They enrolled a TNFi treatment group from one single-centre cohort and a conventional NSAID treatment group from another single cohort to analyse the effect of TNFi on radiographic progression. However, as mentioned in their limitation, they also have a problem with 'confounding by indication', as patients had significantly different baseline characteristics between periods exposed and not exposed to TNFi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Park et al showed that early TNFi treatment can reduce radiographic progression by inflammation control. 15 They enrolled a TNFi treatment group from one single-centre cohort and a conventional NSAID treatment group from another single cohort to analyse the effect of TNFi on radiographic progression. However, as mentioned in their limitation, they also have a problem with 'confounding by indication', as patients had significantly different baseline characteristics between periods exposed and not exposed to TNFi.…”
Section: Discussionmentioning
confidence: 99%
“…3 5 14 15 A high inflammation level at TNFi initiation and long-term TNFi use appear to reduce radiographic progression in a longitudinal cohort study. [14][15][16][17] Real-world evidence refers to clinical evidence obtained from the analysis of real-world data to determine drug effects. 18 We expected that with respect to chronic diseases, a study investigating the relationship between drug effects and ankylosis using various healthcare data accumulated over a long period of time, mainly from electronic medical records (EMRs), will provide real-world evidence from patients with AS.…”
Section: Spondyloarthritismentioning
confidence: 99%
“…Smoking and CRP level was not captured as having a significant association with radiographic progression in our study, and it depends partly on the multivariable models, design of studies and/or cohorts [23,33]. Influence of smoking on radiographic progression was further determined by its dose and the interaction with baseline syndesmophyte(s) and inflammation [23,34].…”
Section: Discussionmentioning
confidence: 83%
“…Influence of smoking on radiographic progression was further determined by its dose and the interaction with baseline syndesmophyte(s) and inflammation [23,34]. Use of TNF inhibitors can effectively suppress the inflammation, leading to the decrease in the radiographic progression regardless of baseline CRP level [33,35]. In this study, over a half of the patients (n=101, 57.4%) received TNF inhibitors and use of TNF inhibitors was marginally associated with the slowed progression (OR [95% CI] 0.39 [0.15, 1.01], p=0.052; Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…All these events caused by inflammatory conditions have been the major reasons of back pain affecting people (19). Recent studies have pointed out that increased inflammatory conditions strongly affect the efficacy of surgical intervention in the affected spinal areas and the recovery period after surgery (21). Evaluation of the inflammatory condition may allow important predictions of the effectiveness of the surgical procedure and postoperative recovery (28).…”
mentioning
confidence: 99%